(untitled) (Research, Society and Development, 2022)
Anticoagulants are highly efficient drugs, however, their use must be analyzed in terms of pharmacological aspects and therapeutic monitoring is crucial and healthy in cases of venous thromboembolism (VTE). Therefore, this study aims to address the pharmacological aspects and how therapeutic monitoring should be carried out in the use of oral anticoagulants in cases of VTE, analyzing studies on the subject. For this, a literature review was carried out, based on studies dated from 2016 to 2022, from scientific databases of studies on the subject, through a narrative literature review. Ten articles were selected. Among the results, it was seen that the ten articles highlighted in the table emphasize types of oral anticoagulants, which varied according to studies, thus achieving the objectives of the study, demonstrating that the new generation of anticoagulants works to direct a specific step of the coagulation cascade and with the possibility of replacing common pharmacological treatments, bringing greater safety and reduction of side effects. Concluding that anticoagulant therapy was based almost exclusively on the use of heparin, but that over the last few decades, more studies have been developed and new classes of anticoagulant drugs have significantly changed the therapeutic arsenal, bringing greater efficacy and safety in relation to conventional treatment within of the clinical context.